S99 Point of care testing for respiratory viruses (RPOCT): a novel service to facilitate appropriate discharge and infection control measures and improve antimicrobial stewardship. (December 2018) - Roy, K; Groom, K; Read, N; Cucciniello, C; Knight, M
Abstract : Introduction: Respiratory infection, predominantly due to viral pathogens, poses a huge burden on the NHS especially during winter. An earlier definitive microbiological diagnosis should allow more rapid clinical decision-making on aspects of care, including hospital admission (versus discharge) and antibiotic use, and prevention of nosocomial infection. We hypothesised that use of RPOCT would improve the quality of service by guiding early management plans, improving bed flow and infection control within the Trust and reducing morbidity associated with empirical antibiotic prescribing. Objectives: To investigate whether an RPOCT service in ED/AAU would result in: Earlier definitive microbiological diagnosis Improved antimicrobial stewardship Early safe discharge (in appropriate cases) Reduced nosocomial infection and bed closures for infection control purposes. Methods: We present 1075 patients who underwent RPOCT (BioFire Film Array, Biomerieux Inc.) from 15 January to 1 May 2018 when presenting with respiratory and/or generalised viral symptoms. Results: A positive viral result was noted in 61% of tests, of which only 56% were positive for Influenza and the rest for other viruses. Time from ED admission to result was significantly shorter with RPOCT versus conventional laboratory methods (6.5 versus 44.4 hours: P<0.001). RPOCT findings were integrated with other key clinical indices (figure 1) and clinical outcomes shown. 121 patients were identified as potentially suitable for discharge without antibiotics (normal CXR, low CRP in absence of bacterial infection). Of 50 influenza cases, 22 who had been tested in ED had no subsequent bed moves as opposed to 28 tested outside ED where there were 14 bed moves some resulting in closure of bays or beds (P<0.001). Conclusions: We have demonstrated that RPOCT permits more informed early decision-making, likely to improve the patient journey and was associated with avoidance of bed and ward closures with potential reduction in nosocomial transmission of infection. Integration of RPOCT results with other clinical information can help identify cohorts among whom some patients may be appropriate for avoidance of antibiotic use and/or avoidance of hospital admission – patients considered suitable for these approaches had good outcomes at short term follow-up.